Does Nutritional Status Affects Oral Health Related Quality of Life Among Elderly? A Cross-Sectional Study at A Tertiary Care Health Centre, Rishikesh, India - Mahendra Singh; Abhishek Sharma; Sujal M Parker; Yogesh Arvind Bahurupi; Pradeep Aggarwal; Rohit Katre (Medsci Publications, 2022)
Aim: Present study was conducted to evaluate the impact of nutritional status on oral health related quality of life using Geriatric Oral Health Assessment Index (GOHAI) among geriatric population attending outpatient department (OPD) of tertiary health care centre in Rishikesh. Settings and Design: Present cross-sectional study was conducted on geriatric male & female participants attending Outpatients Department (OPD) of tertiary care centre, RISHIKESH. Methods and Material: Nutritional assessment was recorded by using Mini Nutritional Assessment (MNA) tool. Oral health related quality of life was assessed using pre-validated Hindi version of Geriatric Oral Health Assessment Index (GOHAI) questionnaire. Statistical analysis: Kruskal-Wallis and Mann-Whitney U test were applied using SPSS 22.0 Software. Logistic regression analysis was done to find out risk factors. Results: A total of 281 participants completed the questionnaire with mean age of 66.89 ± 6.43 years. About three fourth (73%) of total participants were at risk of malnourishment. A statistically significant difference (P=0.005) was observed when the median GOHAI scores were compared with nutritional status (MNA scores). Conclusions: A statistically significant difference was found between nutritional status and geriatric oral health related quality of life (GOHAI). Nutritional status affects oral health related quality of life among elderly population.